0672 The Effect Of Armodafinil On Sleep Spindles In Obstructive Sleep Apnea: Secondary Analysis Of A Randomized Placebo-controlled Trial. (27th May 2020) - Emami, L; Marshall, N S; Chapman, J L; Cho, G; Grunstein, R R; Yee, B J; D'Rozario, A L
Abstract: Introduction: Armodafinil has been trialed in OSA patients to promote wakefulness and simulated driving performance. We have previously completed a 6-month trial of 150mg of armodafinil vs placebo in moderate-severe OSA patients not using CPAP (ACTRN# 12611000847910) observing that participants on armodafinil learned to perform better across a 90-minute driving simulator task faster than those on placebo. It is possible that this reduction in time-on-task decrement may have been due to increased learning on armodafinil. Sleep spindles have previously been implicated in procedural learning and neurobehavioral performance. We hypothesized that armodafinil increases sleep spindle events during NREM sleep to enhance learning. Methods: Sixty-three overweight severe OSA patients (mean BMI: 32.3kg/m2 (26.1-42.5); age 53.1 years (28-71), 52 males) underwent overnight in-lab polysomnography at baseline (0 months) and at a 6-month follow-up. All-night EEG signals were analyzed using a previously validated automated spindle detection algorithm. EEG recordings were visually inspected by an experienced sleep physician (LE), who was blinded to drug allocation. To minimize the likelihood of type 1 error we selected three key spindle variables detected at Cz for analysis of change between 0 and 6 months: 1) total number of spindle events (11-16 Hz) in NREM sleep 2) density of slow spindles (≥11 to ≤ 13Hz) per minute of NREM sleep, and 3) fast spindle density in NREM (>13 to ≤ 16Hz). Results: The change in total spindle count in NREM sleep (armodafinil=11.6 vs Placebo =-17.1, p=0.57), fast spindle density (armodafinil=0.06 vs Placebo =-0.02, p=0.63) and slow spindle density (armodafinil=-0.00 vs. Placebo =-0.03, p=0.74) were not increased by armodafinil. Conclusion: If armodafinil enhances simulated driving performance in a way that suppresses time-on-task effects it does not appear to be through a sleep spindle enhancing mechanism. Armodafinil is probably not a pharmacological method of enhancing sleep spindles. Support: World Sleep Society (International Sleep Research Training Program)CIRUS, Centre for Sleep and Chronobiology, Woolcock Institute of Medical Research, University of Sydney